The Influence of Personal Characteristics, Knowledge Management and Organizational Support on Work-Life Balance in Hospitals - Pinondang Nainggolan; Syaifuddin; Fajar Rezeki Ananda Lubis (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2025)
The decrease in the number of patient visits to one of the hospitals is caused by various important factors. Among them may be due to a poor service system. Therefore, this study will examine the Influence of Personal Characteristics, Knowledge Management and Organizational Support on Work-Life Balance. Data collection in the study used literature studies and quantitative descriptive. Data collection was carried out at the Bhayangkara Level II Hospital in Medan. The research sample was 220 people. The results of the study showed that personal characteristics, knowledge management and organizational support had a positive effect on work-life balance at the Bhayangkara Level II Hospital in Medan. So it is concluded that all independent variables have an influence on Work-Life Balance at the Bhayangkara Level II Hospital in Medan.